Study on transient reaction mechanism and explosion intensity parameters of micron-sized flake aluminum dust in air. (31st December 2021) - Jing, Qi; Wang, Dan; Liu, Qingming; Ren, Lingxiao; Wang, Yanfu; Liu, Changqi; Shen, Yang; Wang, Zhisong
Graphical abstract: Highlights: The optimal explosive concentration of flake aluminum powder in air is about 400 g/m 3 . The maximum pressure rise rate of flake aluminum dust explosion in air reaches 1560 bar/s. The highest flame temperature of flake aluminum dust explosion in air is about 3500 K. Part of the spherical Al2 O3 product adheres to the surface of the flake aluminum dust. The incomplete combustion of flake aluminum dust is its inherent character. Abstract: Micron-sized flake aluminum dust has great potential in rocket propellants and advanced thermobaric weapons because of its large specific surface area. A 20 L near-spherical explosion system and a 2D simulation model are established to study the explosion intensity parameters and transient reaction details of flake aluminum dust/air two-phase explosion. The transient reaction rate of flake aluminum dust/air is mainly determined by the oxygen diffusion rate and chemical kinetic rate. Nano-sized Al2 O3 products have two distribution states: some particles are dissociated in the explosion container and gradually collide and agglomerate to form a pure product block; others adhere to the surface of flake aluminum dust, which hinders the further contact between aluminum dust and air. The maximum explosion overpressure (9.16 bar) occurs when the aluminum dust concentration is about 400 g/m 3, and the maximum pressure rise rate of flake aluminum dust explosion can reach 1560 bar/s. A colorimetric thermometer is used to record the flame temperature of the gas/dust two-phase explosion and the highest flame temperature is about 3500 K. This work will provide reference for explosion protection and efficient utilization of flake aluminum dust.